Molecular Electronics – Integration of Single Molecules in Electronic Circuits - Marcel Mayor; Heiko B. Weber (CHIMIA, 2002)
Electronic devices made with organic molecules may one day play an important role in integrated circuits. However, the research is still in its infancy. The mechanically controlled break-junction technique allows the measurement of the current through a single molecule junction. The current–voltage relations indicate a nonlinear conductance. Information about the junction can be provided by comparative studies of different molecules. It turns out that the conduction properties depend strongly on the molecular structure. This, in turn, encourages the idea of tailoring the electronic properties by an appropriate design of the molecule.